Jewish Roots of Eastern Christian Mysticism : Studies in Honor of Alexander Golitzin - Orlov, Andrei A., (Vigiliae Christianae, Supplements ;, 2020)
The essays collected in Jewish Roots of Eastern Christian Mysticism intend to honor Alexander Golitzin, a scholar known for his keen attention to the Jewish matrix of Eastern Orthodox spirituality. Following Golitzin's insights, this Festschrift explores influences of Jewish apocalypticism and mysticism on certain early and late Christian authors, including Irenaeus, Origen, Evagrius of Pontus, Pseudo-Dionysius, and Symeon the New Theologian. Special attention is given to Jewish theophanic traditions regarding the beatific vision of the divine Glory (Kavod), which profoundly shaped Eastern Christian theology and liturgy. This volume demonstrates that recent developments in the study of apocalyptic literature, the Qumran Scrolls, Gnosticism, and later Jewish mysticism throw new and welcome light on the sources and continuities of Orthodox theology, liturgy, and spirituality